Research on cross-country-skiing: where we're coming from, where we are and where we're going - Holmberg, H. C. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
Our long tradition of research on cross-country skiing in connection with exercise science has taken advantage of the extraordinary physical capacities and unique quadripedal patterns of movement of the athletes involved. Such investigations of physiological and biomechanical responses have not only provided new insights into the factors that limit human performance, but also new knowledge about physiology, biomechanics and motor control in general.